If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6b + -38 = -6b + 14 Reorder the terms: -38 + 6b = -6b + 14 Reorder the terms: -38 + 6b = 14 + -6b Solving -38 + 6b = 14 + -6b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '6b' to each side of the equation. -38 + 6b + 6b = 14 + -6b + 6b Combine like terms: 6b + 6b = 12b -38 + 12b = 14 + -6b + 6b Combine like terms: -6b + 6b = 0 -38 + 12b = 14 + 0 -38 + 12b = 14 Add '38' to each side of the equation. -38 + 38 + 12b = 14 + 38 Combine like terms: -38 + 38 = 0 0 + 12b = 14 + 38 12b = 14 + 38 Combine like terms: 14 + 38 = 52 12b = 52 Divide each side by '12'. b = 4.333333333 Simplifying b = 4.333333333
| 3(2x+1)=4x-13 | | 54=(4r-5) | | 8(f+8)=1 | | 2a-5(a-4)=-4 | | X+3x-12=180 | | 7=2t-5 | | X(3x-12)=180 | | 4x+(5+2x)=2 | | 5x+18-4=-36 | | x^2+6-30=0 | | 2r-45-19r=-53+r | | w-6=-48 | | y=4+(-2) | | -10-6x+4x=3-4x-1 | | 2x+y=39.50 | | w-6=48 | | y=8-3/4(-1) | | 4=6(x-2)-8x | | .5(3x+6)=1.1-(x+2) | | y=8-3/4(1) | | 15x-8y=138 | | y=8-3/4(0) | | 7(y-8)+24=-27(y-6) | | -5p=-8p+3p | | -2x-(4+x)=2 | | n=-70 | | (5x+10)+(6x)=180 | | -6(x-8)=-54 | | -9(c+1)=5 | | 3.(x-2)=2x-4 | | 3a-24= | | 7y-32=-27y-6 |